2012
DOI: 10.1111/j.1447-0756.2012.02055.x
|View full text |Cite
|
Sign up to set email alerts
|

Cord blood ischemia‐modified albumin: Is it associated with abnormal Doppler findings in complicated pregnancies and predictive of perinatal asphyxia?

Abstract: Aim: To evaluate the significance of the cord blood ischemia-modified albumin (IMA) level as a diagnostic marker for perinatal asphyxia and to determine the associations of IMA levels with the complexity of pregnancy and abnormal Doppler findings, regardless of perinatal asphyxia. Methods: This prospective study included 169 newborns, sixteen of whom had perinatal asphyxia and 33 who were from complicated pregnancies. Doppler measurements were obtained from the uterine, umbilical and middle cerebral arteries, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…The mechanism of IMA generation remains unexplained. It has been suggested that IMA is a modification of serum albumin, and it results from oxidative stress and concurrently produced superoxide-free oxygen radicals that occur during ischemic events, regardless of tissue specificity [7][8][9]12]. Recently, some studies have reported that IMA has a relationship with various ischemia-related conditions, such as acute coronary syndrome, ischemia of liver, brain, kidney, and bowel in adults [7,15,16].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The mechanism of IMA generation remains unexplained. It has been suggested that IMA is a modification of serum albumin, and it results from oxidative stress and concurrently produced superoxide-free oxygen radicals that occur during ischemic events, regardless of tissue specificity [7][8][9]12]. Recently, some studies have reported that IMA has a relationship with various ischemia-related conditions, such as acute coronary syndrome, ischemia of liver, brain, kidney, and bowel in adults [7,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, infants with RDS expose to severe hypoxia [4]. Current studies have determined that cord blood levels of IMA are higher in perinatal asfixia and complicated deliveries associated with fetal distress, hypoxia, and oxidative stress in newborns [11,12,19,20], and IMA has been declared to be a good marker for diagnosis of asphyxia. RDS is known a severe disease that leads to severe hypoxia and further deleterious neurodevelopmental outcomes of preterm infants and mortality without appropriate respiratory support and surfactant therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is generally accepted that IUGR and fetal hypoxia are currently related to placental insufficiency . In a recently published study, increased cord blood IMA was recognized as a useful biomarker in neonates with perinatal asphyxia …”
mentioning
confidence: 99%